Milton Friedman: A brief obituary - David Laidler (The University of Western Ontario, Department of Economics, 2007)
Milton Friedman is rivaled only by John Maynard Keynes as the most influential political economists of the 20th Century. His approach was that of a classical liberal, rather than a conservative, though this put him on the political right in the United States. Friedman's work demands to be evaluated all of a piece, but his outstandingly important technical contributions to economics influenced the development of the discipline in ways that extended far beyond the purview of any particular political agenda.
Keywords: 330; Wirtschaftswissenschaft; Dogmengeschichte; Monetarismus; Chicago-Wettbewerbstheorie